Web-based survey to evaluate the prevalence of chronic and subacute cough and patient characteristics in Japan. Issue 1 (15th July 2021) - Tobe, Keisuke; Kubo, Takekazu; Okuyama, Kotoba; Kikuchi, Masashi; Chen, Yirong; Schelfhout, Jonathan; Abe, Machiko; Tokita, Shigeru
Abstract : Background: Cough lasting 3–8 weeks and more than 8 weeks are defined as subacute/prolonged cough and chronic cough, respectively. Japanese chronic cough population has not been well studied. This study aimed to describe the prevalence and characteristics of chronic cough and subacute cough patients in Japan. This study also sought to compare between chronic cough patients who were not greatly satisfied with treatment effectiveness for resolving cough and other chronic cough patients. Methods: Data from a cross-sectional online 2019 Japan National Health and Wellness Survey and a supplemental chronic cough survey were used to understand respondents' chronic cough status and their cough-specific characteristics and experience. The prevalence, patient characteristics and cough-specific characteristics were summarised descriptively. Patients who were not greatly satisfied with treatment effectiveness and other chronic cough patients were compared for their characteristics and cough severity. Results: The point prevalence of chronic cough was 2.89% and 12-month period prevalence was 4.29%. Among all chronic cough patients analysed, the average age was 56 years old, 61.1% were males and 29.4% were current smokers. Patients were most frequently told by a physician that cough was related to allergic rhinitis, asthma and cough variant asthma. Only 44.2% of chronic cough patients had spoken with a physician about their cough, and half of chronic cough patients did not use any medications. Patients who were not greatly satisfied with treatment effectiveness had significantly greater cough severity during past 2 weeks compared with other chronic cough patients (Visual Analogue Scale 45.34 vs 39.63). Conclusions: This study described the prevalence and patient characteristics information of chronic cough patients in Japan. Furthermore, the study highlighted an unmet need for better diagnosis and treatments for chronic cough patients, especially among patients who were not greatly satisfied with treatment effectiveness and reported significantly worse cough severity.